Social Protection for poor, vulnerable and disadvantaged groups - Brzeska, Joanna; Das, Mousumi; Fan, Shenggen (Emerald Publishing Limited, 2015)
– The purpose of this paper is to identify the pathways through which social protection policies in China and India can address the key challenges facing poor, vulnerable, and disadvantaged groups under rapid transformation in both countries.– This paper reviews the main social protection policies in China and India and analyzes the challenges that they are facing. This analysis is based on an evaluation of poverty and food security trends in both countries among vulnerable and disadvantaged groups followed by an overview of major experiences and gaps in social protection policies in the two emerging Asian giants.– Improving the coverage and targeting of social protection systems is vital, and will require a multi-faceted reform portfolio that promotes more integrated and horizontally equitable systems. Emphasis should be placed on developing productive, cross-sectoral social protection programs that combine short-term social safety support with long-term tools to enhance productivity, paying special attention to nutrition, health, and human capital development. More efficient coverage and targeting should bridge the rural and urban divide and be grounded in transparent criteria and procedures that govern program implementation at all levels of the government. As both countries become more urbanized, social protection programs need to give equal attention to emerging food insecurity and nutrition issues within urban areas without detracting from food security and nutrition efforts in rural areas.– Faced with a sizable population of undernourished and poor people, India and China have applied rather different approaches to address food insecurity. The originality and value of this paper lie in an in-depth parallel analysis of how China and India can better use their social protection systems to address food insecurity and undernutrition among poor, vulnerable, and disadvantaged groups.